UPAYA KEBERATAN DALAM PENGADAAN BARANG/JASA PEMERINTAH DIKAITKAN DENGAN PRINSIP DALAM GOVERNMENT PROCUREMENT AGREEMENT - Budi Yulianto, Arief (Veritas et Justitia, 2017)
The Government Procurement Agreement (GPA), as part of agreements made within the purview of the  World Trade Organization (WTO), opens up the doors for foreign businesses to enter the domestic market of government procurement (goods/services).  Indonesia at present does not yet signed the GPA but decided to become an observer instead. Consequently, the government decides to harmonize its national laws regulating government procurement mechanism or procedure with the international standard (GPA). This article shows that there still exist a huge difference in how the national law regulates the public auction procedure (complaints, challenges and dispute resolution mechanism) with the GPA, which is used as a reference.  This situation should be dealt with should Indonesia decides to sign and ratify the GPA.